Integrated Research as Key to the Development of a Sustainable Geothermal Energy Technology. Issue 7 (18th April 2017) - Meller, Carola; Bremer, Judith; Baur, Sabine; Bergfeldt, Thomas; Blum, Philipp; Canic, Tina; Eiche, Elisabeth; Gaucher, Emmanuel; Hagenmeyer, Veit; Heberling, Frank; Held, Sebastian; Herfurth, Sarah; et al.
Abstract: As estimated by the International Energy Agency, geothermal power can contribute to 3.5 % of worldwide power and 3.9 % to heat production by 2050. This includes the development of enhanced geothermal systems (EGSs) in low‐enthalpy systems. EGS technology is still in an early stage of development. Pushing EGS technologies towards market maturity requires a long‐term strategic approach and massive investments in research and development. Comprehensive multidisciplinary research programs that combine fundamental and applied concepts to tackle technological, economic, ecological, and safety challenges along the EGS process chain are needed. The Karlsruhe Institute of Technology (KIT) has defined a broad research program on EGS technology development following the necessity of a transdisciplinary approach. The research concept is embedded in the national research program of the Helmholtz Association and is structured in four clusters: reservoir characterization and engineering, thermal water circuit, materials and geoprocesses, and power plant operation. The proximity to industry, closely interlinked with fundamental research, forms the basis of a target‐orientated concept. The present paper aims to give an overview of geothermal research at KIT and emphasizes the need for concerted research efforts at the international level to accelerate technological breakthrough of EGS as an essential part of a future sustainable energy system. Abstract : Harnessing underground power : The Karlsruhe Institute of Technology (KIT), located within the Upper Rhine Graben, takes advantage of favorable geothermal conditions and has defined a comprehensive research program on enhanced geothermal systems technology development following the necessity of a transdisciplinary approach. Research activities cover the whole process chain, including system integration, and span from fundamental to applied research across scales.